Effective and Immersive Teleoperation with Real-World Constraints - Geary, Brendan; Towle, Bradford (Journal of Games, Game Art, and Gamification, 2026)
This study investigates the development of a telepresence system that leverages standard, industry-available hardware to support teleoperation in a cost-effective and accessible manner. Conventional telepresence solutions often rely on advanced technologies such as 360-degree or stereoscopic cameras, high-end haptic feedback devices, and specialized robotic platforms. While these approaches can deliver highly immersive experiences, they frequently involve significant implementation costs, limited accessibility, or insufficient locomotion support, which restrict their broader adoption. Consequently, there is a critical need for a telepresence method that balances usability, immersion, and affordability while maintaining precise and reliable control mechanisms. The proposed solution integrates commercially available virtual reality (VR) equipment with a mobile robotic platform to construct a virtual environment that enhances user interaction and spatial awareness. Real-time video input from the robot’s onboard camera is projected into the VR environment, enabling users to perceive the remote physical space intuitively. To compensate for hardware limitations, the system incorporates visual cues that represent the robot’s orientation, movement direction, and control latency. These cues play a crucial role in improving situational awareness and assisting users in making informed navigation decisions during teleoperation tasks. The study evaluates the system in terms of control simplicity, precision, and overall usability. Particular emphasis is placed on how the virtual environment mitigates latency effects and provides smooth locomotion feedback, resulting in a fluid user experience. The findings demonstrate that effective telepresence can be achieved using standard hardware, offering a practical alternative to more complex and expensive systems while maintaining immersive and accurate teleoperation capabilities.